Parent-Child Agreement Using the Spence Children's Anxiety Scale and a Thermometer in Children with Autism Spectrum Disorder. (2nd April 2015) - May, T.; Cornish, K.; Rinehart, N. J.
Abstract : Children with Autism Spectrum Disorder (ASD) experience high anxiety which often prompts clinical referral and requires intervention. This study aimed to compare parent and child reports on the Spence Children's Anxiety Scale (SCAS) and a child-reported "worry thermometer" in 88 children aged 8–13 years, 44 with ASD and 44 age, gender, and perceptual IQ matched typically developing children. There were no gender differences in child report on the SCAS and worry thermometers. Results indicated generally good correlations between parent and child self-reported SCAS symptoms for typically developing children but poor agreement in parent-child ASD dyads. The worry thermometer child-report did not reflect child or parent reports on the SCAS. Findings suggest 8–13-year-old children with ASD may have difficulties accurately reporting their anxiety levels. The clinical implications were discussed.